Maternal Separation Modifies the Activity of Social Processing Brain Nuclei Upon Social Novelty Exposure - Mejía-Chávez, Sara; Venebra-Muñoz, Arturo; García-García, Fabio; Corona-Morales, Aleph Alejandro; Orozco-Vargas, Arturo Enrique (Frontiers in Behavioral Neuroscience, 2021)
Maternal separation has been shown to disrupt proper brain development and maturation, having profound consequences on the neuroendocrine systems in charge of the stress response, and has been shown to induce behavioral and cognitive abnormalities. At the behavioral level, maternal separation has been shown to increase offensive play-fighting in juvenile individuals and reduce social interest in adulthood. Since most of the studies that have evaluated the consequences of maternal separation on social behavior have focused on the behavioral analysis, there is a need for a further understanding of the neuronal mechanisms underlying the changes is social behavior induced by maternal separation. Therefore, the aim of the present research was to assess the long-term effects of maternal separation on social interaction behavior and to assess the activity of several brain regions involved in the processing of social cues and reward upon social novelty exposure, using c-Fos immunohistochemistry as a marker of neuronal activity. Male Wistar rats were subjected to 4 h maternal separation during the neonatal period, 9:00 h – 13:00 h from postnatal day 1 to 21, and exposed to social novelty during adulthood. After social novelty exposure, brains were fixed and coronal sections of the medial amygdala, lateral septum, paraventricular nucleus of the hypothalamus, nucleus accumbens and medial prefrontal cortex were obtained for c-Fos immunohistochemistry. Maternally separated rats spent less time investigating the novel peer, suggesting that maternal separation reduces social approach motivation. Furthermore, maternal separation reduced the number of c-Fos positive cells of the medial amygdala, paraventricular nucleus of the hypothalamus, lateral septum, nucleus accumbens and medial prefrontal cortex upon social novelty exposure. These findings suggest that maternal separation can reduce the plastic capacity several brain nuclei, which constitute a physiological basis for the emergence of behavioral disorders presented later in life reported to be linked to early life adversity.